2003
DOI: 10.1080/jmf.13.1.50.53
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glucocorticosteroid administration on fetal movements and biophysical profile scores in normal pregnancies

Abstract: Fetal movements and breathing motion were decreased after glucocorticosteroid administration, as evidenced by biophysical profile scores and kick counts. The decrease in the amniotic fluid index observed after glucocorticosteroid administration may have been the result of decreased fetal breathing and, therefore, decreased efflux of alveolar fluid into the amniotic sac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 8 publications
0
13
1
Order By: Relevance
“…Administration of corticosteroids (betamethasone and dexamethasone) for enhancement of fetal lung maturity is also reported to reduce FM and the fetal heart rate (FHR) variability detected by CTG over the 2 days following administration (10,23,24). To assess whether the decrease in FMs was directly related to corticosteroid use, Jackson et al (24) studied a low‐risk ambulatory population. They found that corticosteroid use was associated with decreased FM by subjective maternal assessment and objective biophysical profile scores.…”
Section: Factors Which Influence the Fm Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of corticosteroids (betamethasone and dexamethasone) for enhancement of fetal lung maturity is also reported to reduce FM and the fetal heart rate (FHR) variability detected by CTG over the 2 days following administration (10,23,24). To assess whether the decrease in FMs was directly related to corticosteroid use, Jackson et al (24) studied a low‐risk ambulatory population. They found that corticosteroid use was associated with decreased FM by subjective maternal assessment and objective biophysical profile scores.…”
Section: Factors Which Influence the Fm Patternmentioning
confidence: 99%
“…Fetal breathing was the biophysical component affected in their study. Decreased fetal breathing results in decreased fetal lung fluid exhalation, which is seen as a reduction in the amniotic fluid index, possibly resulting in decreased FM (24). The pathophysiology of corticosteroid changes in FM and FHR variability is still unclear and has not been definitely proven (10,13,19,24).…”
Section: Factors Which Influence the Fm Patternmentioning
confidence: 99%
“…[5][6][7] Other studies have evaluated the effects of steroids on the biophysical profile; these studies have revealed reductions in fetal movement, breathing, or amniotic fluid index (AFI), resulting in decreased biophysical profile scores. 8,9 The present study investigated the unanticipated effects of betamethasone on fetomaternal blood flow and AFI.…”
Section: Introductionmentioning
confidence: 99%
“…A reactive nonstress test result provides reassurance of fetal well‐being; however, when abnormal, it has a high false‐positive rate of 45% to 75% 9 11 . The fetal heart rate is subject to various dynamic factors, including periodic sleep cycles, medications, and antenatal corticosteroids 12 , 13 . Further evaluation is needed to differentiate between the hypoxic or acidemic fetus versus the sleeping or medicated fetus.…”
Section: Discussionmentioning
confidence: 99%